The Expanded Program on Immunization in Pakistan : Recommendations for Improving Performance - Masud, Tayyeb; Navaratne, Kumari Vinodhani (World Bank, Washington, DC, 2013)
The Expanded Program on Immunization (EPI) in Pakistan protects against eight vaccine-preventable diseases and immunizes children below 23 months of age. The program was implemented under the Ministry of Health (MOH) until July 11, 2011, when amendment 18 to the constitution devolved health as a subject completely to the provinces. Currently, the EPI is managed and implemented at the provincial level with coordination provided by the Ministry of inter provincial coordination. During the last decade, EPI performance has been stagnant with only 40-60 percent of children receiving the vaccines age-appropriately. Vaccine preventable diseases are still a major cause for the high infant and child mortality rates in Pakistan. Evidence suggests that underachievement of the EPI is due to a combination of factors including; inadequate performance in the areas of service delivery, program management, monitoring and evaluation, logistics control, human resources management and financing, as well as community health-seeking behaviors and other demand-side issues. The recommendations include: (i) increasing focus on supervision, monitoring and evaluation, (ii) considering performance-based incentives, (iii) exploring partnerships with the private sector, (iv) expediting polio eradication initiatives, (v) improving management, (vi) increasing targeted capacity development, (vii) concentrating on the target age group for immunization, (viii) developing socially acceptable strategies, (ix) developing a human resource strategy and implementation plan, and (x) improving planning at the local level.